2013
DOI: 10.1371/journal.pone.0069039
|View full text |Cite|
|
Sign up to set email alerts
|

Tumor Site- and Stage-Specific Associations between Allelic Variants of Glutathione S-Transferase and DNA-Repair Genes and Overall Survival in Colorectal Cancer Patients Receiving 5-Fluorouracil-Based Chemotherapy

Abstract: IntroductionOur retrospective cohort study investigated the effect of tumor site and stage on the associations between the allelic variants of glutathione S-transferase (GST) and DNA-repair genes and overall survival (OS) in CRC patients treated with 5-fluorouracil (5-FU)-based adjuvant chemotherapy.Material and MethodsWe genotyped GSTM1, GSTT1, GSTP1 Ile105Val, XRCC1 Arg399Gln, XRCC3 Thr241Met, and XPD Lys751Gln in 491 CRC patients between 1995 and 2001. A Cox proportional-hazards model was used to calculate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…A meta-analysis of 36 case-control studies also detected a relationship between GSTM1 polymorphism and tumor site [ 18 ]. However other studies found no association between the GSTM1 null genotype and CRC clinicopathologic features [ 9 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 93%
“…A meta-analysis of 36 case-control studies also detected a relationship between GSTM1 polymorphism and tumor site [ 18 ]. However other studies found no association between the GSTM1 null genotype and CRC clinicopathologic features [ 9 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 93%
“…In terms of genetic and epigenetic effects, smoking is related to increased DNA damage and reduced repair capacity, 37 and polymorphisms in DNA repair genes have been associated with colorectal cancer survival. 38 Similarly, smoking can induce aberrant DNA methylation, 39 and differential methylation has been associated with rectal cancer recurrence and survival. [40][41][42] However, whether smoking, DNA repair or methylation, and rectal cancer survival are interrelated remains unknown.…”
Section: Mechanismsmentioning
confidence: 99%
“…Previous studies have reported that glutathione S-transferase P1 (GSTP1) and X-ray repair cross-complementing group 1 (XRCC1) genetic variations may influence the efficacy of chemotherapy in various cancers, such as colon cancer, gastric cancer, and ovarian cancer (Khrunin et al, 2010;Ji et al, 2013;Lai et al, 2013;Zaanan et al, 2014). Currently, many studies reported the role of GSTP1 and XRCC1 genetic polymorphisms in the clinical outcome of NSCLC, but the results are inconclusive.…”
Section: Introductionmentioning
confidence: 99%